A Players’ League: Short- and Long-Term Solutions to Contract Holdouts in the NBA - Turkzadeh, Cameron J. (The Columbia Journal of Law & the Arts, 2022)
The business of basketball can be cruel at times. Teams often trade players against the players’ wishes, using them like chess pieces to help the team, not the player, reach its goal. However, in recent years, the NBA has become a “players’ league” as the balance of power in contract negotiations has shifted from teams to players. More than ever before, players are dictating the terms of their contracts because team owners understand that the public pays top dollar to watch the best players perform, many of whom are considered cultural icons with massive marketability. However, this change in bargaining power has also created incentives for players to participate in opportunistic and strategic behavior. With limited earning-power years and a rare, sought-after skillset, players have increasingly engaged in contractual holdouts with the goal of either being traded to a new team or renegotiating their existing contracts for more money. This Note offers a short- and long-term legal framework to deal with the holdout scenario where players refuse to play pursuant to their original agreements until their contractual demands are accepted. Part I examines the key components of the NBA’s structural framework, including the Collective Bargaining Agreement, the Salary Cap, the Uniform Player Contract, Compensation, and Free Agency. Part II defines the player holdout problem, explains the significance of the problem for the NBA and its teams, and clarifies why traditional remedies set by the courts are inadequate to deal with this concern. Part III presents the optimal short-term legal solutions available to teams to address the holdout problem, namely self-help specific performance and liquidated damages, and certain limitations and challenges in enforcing these solutions. Finally, Part IV introduces a long-term, league-wide strategy to prevent holdouts in the future: Player Escrow Accounts.